The winter of our discontent - Steinbeck, John, 1902-1968 (Penguin classics., 2008)
From the Publisher: From a swashbuckling pirate fantasy to a meditation on American morality-two classic Steinbeck novels make their black spine debuts. In awarding John Steinbeck the 1962 Nobel Prize in Literature, the Nobel committee stated that with The Winter of Our Discontent, he had "resumed his position as an independent expounder of the truth, with an unbiased instinct for what is genuinely American." Ethan Allen Hawley, the protagonist of the novel, works as a clerk in a grocery store that his family once owned. With the decline in their status, his wife is restless, and his teenage children are hungry for the tantalizing material comforts he cannot provide. Then one day, in a moment of moral crisis, Ethan decides to take a holiday from his own scrupulous standards.